2013
DOI: 10.1155/2013/213130
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and Pharmacological Treatment in Diabetic Retinopathy

Abstract: Diabetic retinopathy (DR), the most common microvascular complication of diabetes mellitus, is estimated to be the leading cause of new blindness in the working population of developed countries. Primary interventions such as intensive glycemic control, strict blood pressure regulation, and lipid-modifying therapy as well as local ocular treatment (laser photocoagulation and pars plana vitrectomy) can significantly reduce the risk of retinopathy occurrence and progression. Considering the limitations of curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 87 publications
(103 reference statements)
3
71
0
Order By: Relevance
“…This notion is consistent with minimal RORα staining in lectin positive retinal blood vessels ( (21). Increased levels of proinflammatory cytokines were found in vitreous fluid of patients with proliferative retinopathy (22). We next evaluated whether RORα controls pathologic retinal neovascularization through modulation of retinal inflammation.…”
Section: Rorα Deficiency Significantly Attenuated Pathologic Retinalsupporting
confidence: 64%
“…This notion is consistent with minimal RORα staining in lectin positive retinal blood vessels ( (21). Increased levels of proinflammatory cytokines were found in vitreous fluid of patients with proliferative retinopathy (22). We next evaluated whether RORα controls pathologic retinal neovascularization through modulation of retinal inflammation.…”
Section: Rorα Deficiency Significantly Attenuated Pathologic Retinalsupporting
confidence: 64%
“…P53 and Bax play crucial roles in apoptosis, which are in turn critical in pathogenesis in diabetic retinopathy. 11,12 As shown in Figure 2, our results suggested that the protein ( Fig. 2A) and mRNA (Fig.…”
Section: Elevation Of Angptl3 Levels Stimulates Apoptosis and Inflammsupporting
confidence: 59%
“…62 Nonsteroidal anti-inflammatory drugs are a class of drugs that elicit anti-inflammatory effects by inhibiting cyclooxygenase enzyme-mediated prostaglandin formation. 63,64 At high doses, cyclooxygenase-2 inhibitor meloxicam has been shown to reduce endothelial NO synthase concentrations, 62 NF-kB activation levels, 37 and leukocyte adhesion 62 in diabetic retinas. In addition, our study indicates that fenofibrate can reduce high glucose-induced cyclooxygenase-2 up-regulation to exhibit anti-inflammatory effects.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…In addition, our study indicates that fenofibrate can reduce high glucose-induced cyclooxygenase-2 up-regulation to exhibit anti-inflammatory effects. 65 Aspirin has also been shown to significantly reduce the adhesiveness of leukocytes 62 and, at high doses, to minimize the development of microvascular lesions in patients in non-proliferative DR. 64,66,67 Leukocytes have been shown to play a major role in the degeneration of retinal capillaries in DR. 33,34 Leukocyte integrin a m b 2 (alias CD11b/CD18 or MAC1), a protein mediating adhesion between leukocytes and endothelial cells, has been shown to facilitate such damage to endothelial cells by activating leukocytes. 33 Diabetes causes a significant increase in leukocyte adhesion to the retinal microvasculature (leukostasis), and selective antagonism of that adhesion by expression of neutrophil inhibitory factor has been shown to inhibit the diabetes-induced degeneration of retinal capillaries.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%